Outcome of supplementation of vitamin D on intact parathyroid hormone level in chronic kidney disease patients - Adhikary, Laxman Prasad; Khanal, Aarjan (Journal of Kathmandu Medical College, 2019)
Background: Secondary hyperparathyroidism is present in majority of patients with estimated glomerular filtrate rate less than 60 mL/min/1.73 m2. Sustained elevated parathyroid hormone level can cause osteitis-fibrosa-cystica, fracture, hypercalcemia, hyperphosphatemia, and calciphylaxis. Kidney Disease Improving Global Outcome guidelines for Chronic Kidney Disease Mineral and Bone Disorder 2017 recommends treatment with calcitriol or vitamin D analogue if parathyroid hormone level is progressively increasing and remains persistently above the upper limit despite correction of modiﬁable factors. Objectives: The objective of this study was to determine the mean change in intact parathyroid hormone after calcitriol supplementation in patients with chronic kidney disease (stage 3 to 5). Methodology: This prospective observational study enrolled 92 patients with chronic kidney disease stage 3 to 5, not under maintenance hemodialysis. Patients who had intact parathyroid hormone level more than 200 pg/ml, serum phosphate level less than 4.5 mg/dl and corrected serum calcium less than 9.5 mg/dl were selected for the study. They were supplemented with oral calcitriol 0.25μg thrice weekly for three months and intact parathyroid hormone level was measured after three months. Results: Mean intact parathyroid hormone level before supplementation was 332.91 ± 96.046pg/ml and after three months of supplementation with calcitriol was 176.49 ±53.764pg/ml. This finding was statistically significant (Correlation: 0.471, p-value less than 0.05). Thus, supplementation of calcitriol reduced the mean intact parathyroid hormone level in the chronic kidney disease patients in our study. Conclusion: Calcitriol supplementation seems to be an effective measure to reduce intact parathyroid hormone level in chronic kidney disease patients when it remains persistently high despite correction of modiﬁable factors.